Advanced Theories in International Accounting Standards - Hamed, Ameera Fares; Hassan, Hayder Mohammed; Mohammed, Mohammed Talaat; Hatem, Faten (Journal of Ecohumanism, 2024)
Background: Because of the dynamic character of the global corporate world, International Accounting Standards (IAS) have evolved, demanding a continuous reevaluation of the underlying ideas. This academic paper dives into the history of IAS, stressing the expanding complexities and issues faced by financial statement standard setters, preparers, and users in today's global business context. Objective: The fundamental goal of this study is to investigate and examine advanced theories in International Accounting Standards to improve our understanding of its conceptual foundations and implementation. The research tries to uncover gaps in existing theories and suggest creative frameworks to meet emerging concerns by critically reviewing recent advancements. Methodology: The article synthesizes findings from many scholarly publications, regulatory papers, and empirical studies using a complete literature review and comparative analysis. A careful assessment of advanced theories proposed by top researchers and worldwide standard-setting agencies is part of the methodological approach. Results: The article's findings demonstrate a nuanced comprehension of advanced theories, including conceptual frameworks, assessment procedures, and disclosure practices. It is a summary of current arguments that sheds light on the ramifications of using diverse theoretical views in the creation and implementation of International Accounting Standards. Conclusion: By providing a comprehensive summary of advanced theories, this study contributes to the current discussion about International Accounting Standards. The findings highlight the importance of a dynamic and adaptive framework capable of accommodating the evolving complexities of the global corporate environment. This study lays the groundwork for future advances in international accounting theory and practice, paving the way for more robust and effective standards.